Alterations of Lysine Acetylation Profile in Murine Skeletal Muscles Upon Exercise - Liang, Dehuan; Chen, Cheng; Huang, Song; Liu, Sujuan; Fu, Li; Niu, Yanmei (Frontiers in Aging Neuroscience, 2022)
Regular exercise is a powerful regulator of skeletal muscle mass and strength. Lysine acetylation is an important post-translational modification (PTM) involved in a broad array of functions of cell. Muscle proteins contain considerable lysine-acetylated (Kac) sites, so we aim to investigate the effect of exercise-induced lysine acetylation on muscle protein property. We divided twenty male C57BL/6 mice into exercise and control groups randomly. After 6-week treadmill exercise, acetyl-proteome studies were performed with gastrocnemius muscle of mice from two groups to explore the effect of acetylation modification on muscle protein property. A particular map of lysine acetylation sites from skeletal muscle of mice by high-resolution tandem mass spectrometry was provided. A total of 2254 lysine acetylation sites in 693 protein groups were identified, among which 1916 sites in 528 proteins were quantified. Furthermore, the enrichment analysis suggested that proteins acetylation could influence muscle proteins property, including structure and function. Molecular docking results revealed that mimicking proteins deacetylation primarily influenced interaction between substrates and enzymes, which may ultimately affect the catalytic reaction of enzymes. The results showed that exercise-induced lysine acetylation appears to be a crucial contributor to the alteration of skeletal muscle property, suggesting that its modulation is a potential valid approach for preventing skeletal muscle dysfunction.